KARAKTERISTIK BATUAN SEDIMEN HALUS FORMASI SINAMAR UNTUK MENGETAHUI POTENSINYA SEBAGAI BATUAN INDUK DI DAERAH MUARA BUNGO, JAMBI - Heri Hermiyanto Zajuli, Moh.
Research area is located at northwest part of South Sumatra Basin, Muara Bungo Regency, Jambi Province. Location of research occupied 8% of total spreading Sinamar Formation. The Oligocene Sinamar Formation consists of shale, claystone, mudstone, sandstone, conglomeratic sandstone and intercalation coal seams. This research was focused in fine sediment rock of Sinamar Formation, such as shale, claystone, and mudstone. Not many research of source rock in this area has been done before. The primary data was collected from SNM well which has 75 m deep, and outcrop that was analyzed according to total organic carbon (TOC), Rock-Eval pyrolysis, vitrinite reflectance (Ro), organic petrography, Scanning Electron Microscope (SEM), gas chromatography – mass spectometry (GC-MS) of normal alkanes including isoprenoids, triterpanes, and sterane. The biomarker data that used in this research were limited only on common mass ion such as triterpanes (m/z 191) and steranes (m/z 217). Based on analysis results of source rock richness and maturity, shale of Sinamar Formation has good to excellent degree of richness (2% - 10%) as source rock. Source rock richness and maturity of claystone and mudstone are fair. The shale maturity of Sinamar Formation according to Tmax is 4360 C - 4390 C, categorized as early mature stage that has preference to produce oil which comes from type I of kerogen (HI > 600 mg HC/g). Claystone and mudstone have preference to produce gas which comes from type III of kerogen (HI < 300 mg HC/g). Based on the TOC versus Potential Yield diagram, the shale of Sinamar Formation is included into oil prone source rock potential, while claystone and mudstone categorized as gas prone source rock potential. The dominant maceral group is exinite, composed of alginite (3.4 – 18%), resinite (1.6 – 5.6%). Organic petrography, biomarker, and SEM analyses show that organic material of the shale comes from high plants and algae especially botrycoccus species. Botrycoccus, fresh water fish fossil, and trunk found in the shale indicate that the shale was deposited in lacustrine environment. Based on SEM analysis, the shale consists of smectite-illite, illite, kaolinite, organic matter as liptinite/exinite (resinite, alginite) and oil droplets. Shale of Sinamar Formation is categoriezed as potential for source rock. If shale of Sinamar Formation has adequate maturity, the shale of Sinamar Formation on research area will produce oil 5.02 million barrels, while from the total shale of Sinamar Formation arround 6.08 billion barrels.